Pension Reforms in Japan - Kashiwase, Kenichiro; Nozaki, Masahiro; Tokuoka, Kiichi (Washington, D.C. : International Monetary Fund, 2012)
This paper analyzes various reform options for Japan's public pension in light of large fiscal consolidation needs of the country. The most attractive option is to increase the pension eligibility age in line with high and rising life expectancy. This would have a positive effect on long-run economic growth and would be relatively fair in sharing the burden of fiscal adjustment between younger and older generations. Other attractive options include better targeting by 'clawing back' a small portion of pension benefits from wealthy retirees, reducing preferential tax treatment of pension benefit incomes, and collecting contributions from dependent spouses of employees, who are currently eligible for pension benefits even though they make no contributions. These options, if implemented concurrently, could reduce the government annual subsidy and the government deficit by up to 1u percent of GDP by 2020.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet